The legal protection of corals in Malaysia / Fakhriyah Ramli, Kartikha Zainudin, Nurliyana Mokhtaruddin - Ramli, Fakhriyah; Zainudin, Kartikha; Mokhtaruddin, Nurliyana (2011)
This research discussed on the issue of legal protection of corals in Malaysia. The aim of this study is to analyze the comprehensiveness of the current law which protects the corals under the Fisheries Act 1985 and also to further enhance the law regarding the protection of corals in Malaysia. The method used in this research is the qualitative research methodology. The first, method used is library based and internet based. Primary sources and secondary sources were gathered from the UITM law collection library i.e. PTARII. The second method is semi structured interviews with the officers of the Marine Park in Putrajaya and the officers from Reef Check Malaysia who are involved in the protection of corals in Malaysia. The Fisheries Act 1985 (Act 371) is relevant in our country for the protection of corals however the punishment and the enforcement is not sufficient and compared to other countries, the Malaysian law needs further improvement. This study also highlighted some of the problems on coral protection in Malaysia such as destructive fishing methods, waste dumping, marine tourism activities, effect of climate change, impact of cyclone and tsunami, coral bleaching and pollution. Suggestions and recommendations on the protection of corals were also discussed i.e. a specific legislation on corals protection, an increase in the penalty for offenders and the creation of awareness programs for the protection of corals is also highly recommended.